Nutritional status as assessed by nutrient intakes and biomarkers among women of childbearing age – is the burden of nutrient inadequacies growing in America?. Issue 9 (13th October 2014) - Rai, Deshanie; Bird, Julia K; McBurney, Michael I; Chapman-Novakofski, Karen M
Abstract: Objective: Understanding nutrient intakes among women of childbearing age within the USA is important given the accumulating evidence that maternal body weight gain and nutrient intakes prior to pregnancy may influence the health and well-being of the offspring. The objective of the present study was to evaluate nutritional status in women of childbearing age and to ascertain the influence of ethnicity and income on nutrient intakes. Design: Nutritional status was assessed using data on nutrient intakes through foods and supplements from the National Health and Nutrition Examination Survey. Biomarker data from the Centers for Disease Control and Prevention were used to assess nutritional status for selected nutrients. Poverty–income ratio was used to assess family income. Subjects: White ( n 1560), African-American ( n 889) and Mexican-American ( n 761) women aged 19–30 and 31–50 years were included. Setting: A nationally representative sample of non-pregnant women of childbearing age resident in the USA. Results: African-American women had the lowest intakes of fibre, folate, riboflavin, P, K, Ca and Mg. Women (31–50 years) with a poverty–income ratio of ≤1·85 had significantly lower intakes of almost all nutrients analysed. Irrespective of ethnicity and income, a significant percentage of women were not consuming the estimated recommended amounts (Estimated Average Requirement) of several key nutrients: vitamin A (~80 %), vitamin D (~78 %) and fibre (~92 %). Nutrient biomarker data were generally reflective of nutrient intake patterns among the different ethnic groups. Conclusions: Women of childbearing age in the USA are not meeting nutrient intake guidelines, with differences between ethnic groups and socio-economic strata. These factors should be considered when establishing nutrition science advocacy and policy.